As cláusulas adverbiais e as redes sociais em Mariana (MG): um estudo a partir de uma abordagem funcionalista - Danubia Aline Silva (2009)
Taking theoretical basis on functionalist assumptions this present essay had the objective describing the exhaustively the adverbial clauses, specially the stray adverbial clauses, in on a corpus made of data in actual Portuguese language the territory of Mariana. MG The present linguist analysis was developed through one the functionalist syntax. Taking the basis on sociolinguist classification of the informers, linked to social order factors, one can see the social weak net and the strong one. This was done, according to the thought and of Milroy (1987) and Milroy (1992) methodology. Among the factors one can put in evidence the social network factor following the thought and methodology of Milroy (1987) and Milroy (1992). Considering the universality of factors like age, sex, four informers were interviewed. They lived near the city Mariana. The adverbial clause found in the corpus were classified in 08(eight) groups of semantics relations: motive/cause, time, finality, condition, permition, way, conformity and comparison. In both social nets, the adverbial more frequent was the relation of confirmed the results in Lima (2002). In the weak net, (college Net), the presence of adverbial clauses was more expensive. From the total of units of information in this Net, 431 adverbial clauses were identified. On the contrary, in the strong ( Families Net) 390 adverbial clauses of this kind were identified. Related to the number of presences of stray adverbial clauses in the corpus, the result indicates one. that the phenomenon of stray was showed more frequently in the strong social Net. The social like age and sex factors seems not to have importance to the construction of the stray adverbial clauses in the researches that were done.